Evaluation of helmet and goggle designs by modeling non-penetrating projectile impacts. Issue 3 (17th February 2019) - Friedman, Rinat; Haimy, Ayelet; Epstein, Yoram; Gefen, Amit
Abstract: Despite the progress in developing personal combat-protective gear, eye and brain injuries are still widely common and carry fatal or long-term repercussions. The complex nature of the cranial tissues suggests that simple methods (e.g. crash-dummies) for testing the effectiveness of personal protective gear against non-penetrating impacts are both expensive and ineffective, and there are ethical issues in using animal or cadavers. The present work presents a versatile testing framework for quantitatively evaluating protective performances of head and eye combat-protective gear, against non-penetrating impacts. The biomimetic finite element (FE) head model that was developed provides realistic representation of cranial structure and tissue properties. Simulated crash impact results were validated against a former cadaveric study and by using a crash-phantom developed in our lab. The model was then fitted with various helmet and goggle designs onto which a non-penetrating ballistic impact was applied. Example data show that reduction of the elastic and shear moduli by 30% and 80% respectively of the helmet outer Kevlar-29 layer, lowered intracranial pressures by 20%. Our modeling suggests that the level of stresses that develop in brain tissues, which ultimately cause the brain damage, cannot be predicted solely by the properties of the helmet/goggle materials. We further found that a reduced contact area between goggles and face is a key factor in reducing the mechanical loads transmitted to the optic nerve and eye balls following an impact. Overall, this work demonstrates the simplicity, flexibility and usefulness for development, evaluation, and testing of combat-protective equipment using computational modeling. Highlights: A finite element head model was developed for testing head gear. Reduced helmet's outer layer elastic and shear moduli lowered intracranial stresses. Gear material properties could not fully predict impact-related stress in the brain. Reduced goggles-face contact lowered transmitted loads to the optic nerve and eyes.